Generalized probabilistic model allowing for various fatigue damage variables. (July 2017) - Correia, José; Apetre, Nicole; Arcari, Attilio; De Jesus, Abílio; Muñiz-Calvente, Miguel; Calçada, Rui; Berto, Filippo; Fernández-Canteli, Alfonso
Highlights: A generalization of the Castillo-Canteli probabilistic fatigue model is proposed. Generalized fatigue damage variables are proposed keeping original model structure. Fatigue damage parameters for uniaxial and multiaxial loading conditions are discussed. Experimental fatigue data demonstrated appropriateness of proposed generalization. Abstract: This paper proposes a generalization of the Castillo and Fernández-Canteli probabilistic fatigue model and shows how most fatigue models can be obtained as particular cases. Models that include mean-stress effects and multiaxial loading conditions are considered as examples of this general framework. Several fatigue damage parameters such as the Smith-Watson-Topper, the Walker-like strain, energy-based parameter in uniaxial and multiaxial loading conditions, and multiaxial critical plane parameters are proposed as reference parameters for the probabilistic model. It is shown that the Castillo & Fernández-Canteli probabilistic approach can be successfully extended to these advanced fatigue models.